2022
DOI: 10.1007/s11356-022-19328-2
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Economic policy uncertainty and commodity market volatility: implications for economic recovery

Abstract: As a consequence of the COVID-19 pandemic outbreak, most commodities experienced significant price drops, which were expected to continue well into 2020. As a result, the Markov switching model is used to study the influence of policy uncertainty and the COVID-19 pandemic on commodity prices in the USA. Commodity markets are stimulated by economic policy uncertainty, according to results from a two-state Markov switching model. In both high and low regimes, economic policy uncertainty (EPU) influences the comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 93 publications
(88 reference statements)
1
4
0
Order By: Relevance
“…The comparison results show that the time-varying effects of WPU on the commodity prices of minerals, non-ferrous metals, energy and steel metals are differentiated, and the WPU has the largest time-varying effects on the commodity prices of minerals and the smallest time-varying effects on the commodity prices of steel. The empirical results verify the research hypothesis H3, and is consistent to Xiao et al ( 53 ) finding as the impact of steel stands at 0.012%, suggesting that compared to other commodities, steel is the least affected by the epidemic.…”
Section: Resultssupporting
confidence: 90%
“…The comparison results show that the time-varying effects of WPU on the commodity prices of minerals, non-ferrous metals, energy and steel metals are differentiated, and the WPU has the largest time-varying effects on the commodity prices of minerals and the smallest time-varying effects on the commodity prices of steel. The empirical results verify the research hypothesis H3, and is consistent to Xiao et al ( 53 ) finding as the impact of steel stands at 0.012%, suggesting that compared to other commodities, steel is the least affected by the epidemic.…”
Section: Resultssupporting
confidence: 90%
“…Uncertainty in many areas and demand-supply mismatch owing to war like situations (for past 62 years) fuelled the price volatility of these commodities. Sometimes, the impact is not direct, however, the impact is due to disruption of the global and domestic supply chain [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ahmed and Sarkodie [47], Foroni et al [48], and Xiao et al [49] modeled the performance of agricultural and energy prices with the impact of news sentiment related to economic policy uncertainty [50] and pandemic news (COVID-19) sentiment. All these authors found that agricultural and energy commodities are negatively affected by an increase in economic policy-related uncertainty, and only the agricultural ones had a bad performance when the bad sentiment related to news of COVID-19 increased.…”
Section: Literature Reviewmentioning
confidence: 99%